Engineering the Irish Software Tiger. - Ryan, Kevin (Computer (00189162), 2008)
This article discusses the economic strategies and software development priorities established in Ireland. The encouragement of the so-called Celtic tiger, a development boom in Ireland fueled by that country's increasing prominence in the computer programming industry, by the Irish government is described. The coordination of software development priorities by organizations including the Irish Software Engineering Research Centre (Lero), The Ireland Industrial Development Authority, and the Science Foundation Ireland is explored. Efforts to modify the Irish position in the computer programming outsourcing industry to accommodate rising labor costs in Ireland are discussed.